2012
DOI: 10.1111/j.2040-1124.2012.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretory capacity and insulin sensitivity in impaired fasting glucose in Japanese

Abstract: Aims/Introduction:  Impaired fasting glucose (IFG) increases the risk of developing diabetes mellitus (DM). This study was carried out to characterize Japanese patients who have fasting glucose levels (FPG) between 100 and 109 mg/dL (IFG100–109).Materials and Methods:  A total of 1383 Japanese participants were examined by oral glucose tolerance test. We compared insulin secretory capacity (insulinogenic index) and insulin sensitivity (ISI composite) of IFG100–109/normal glucose tolerance (NGT; 100 ≤ FPG < 110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, pre‐diabetes in a Japanese population is both characterized by lower insulin secretion and lower insulin resistance compared with Western populations 16 . Mitsui et al 17 …”
Section: Discussionmentioning
confidence: 99%
“…However, pre‐diabetes in a Japanese population is both characterized by lower insulin secretion and lower insulin resistance compared with Western populations 16 . Mitsui et al 17 …”
Section: Discussionmentioning
confidence: 99%
“…FPG levels showed the highest association with ISI composite in isolated IFG group and secondly with insulinogenic index in multivariate regression analyses. Prospective study reported that insulin sensitivity in isolated IFG subjects was significantly reduced compared with that in NGT subjects prior to the development and diagnosis of isolated IFG [ 28 , 32 34 ]. In this study, insulin sensitivity was lower in isolated IFG group than isolated IGT group and mean BMI of isolated IFG group was higher than isolated IGT group both within the normal range (BMI < 25).…”
Section: Discussionmentioning
confidence: 99%
“…This model might well explain why there is a higher proportion of isolated IGT in isolated impaired fasting glucose (IFG), IFG/IGT, and isolated IGT in Asia than that found in Europe [ 37 , 38 ]. We previously demonstrated in Japanese that the IGI is significantly reduced from NGT via isolated IGT to T2DM, while HOMA-IR is slightly but not significantly increased from isolated IGT to T2DM [ 39 , 40 ]. In addition, we also demonstrated that HOMA-IR is significantly increased from NGT via isolated IFG to T2DM along with a significant reduction in IGI [ 40 , 41 ].…”
Section: Insulin Secretion and Resistance In East Asiansmentioning
confidence: 99%
“…We previously demonstrated in Japanese that the IGI is significantly reduced from NGT via isolated IGT to T2DM, while HOMA-IR is slightly but not significantly increased from isolated IGT to T2DM [ 39 , 40 ]. In addition, we also demonstrated that HOMA-IR is significantly increased from NGT via isolated IFG to T2DM along with a significant reduction in IGI [ 40 , 41 ]. While conversion rates from NGT to T2DM via isolated IGT, IFG/IGT, and isolated IGT need to be compared between Asians and Caucasians prospectively in the future, the model also underlie the appearance of diabetes in East Asians when not nearly as obese as Caucasian [ 5 ••, 42 ] as well as the increased T2DM prevalence among East Asian people such as Japanese Americans in the USA who consume similar daily energy but significantly more fats and less carbohydrates than their counterparts in Japan [ 43 , 44 ].…”
Section: Insulin Secretion and Resistance In East Asiansmentioning
confidence: 99%